Do consumption values in heritage food play a role in the development of behavioural intentions? - Saad, Mazni; Kamarizzaman, Nur Assyiqin; Ishak, Noriza; James Pratt, Thomas (e-International Publishing House, U.K., 2021)
This study explores the state of tourists' perception of Pahang heritage food. This study obtained data from 164 tourists through social media applications. The survey outcomes were encouraging, which showed a positive and significant influence regarding food consumption values and domestic tourist behavioural intentions to consume heritage foods. These findings will help Pahang's destination managers better understand how to promote heritage foods to attract future domestic tourism. Marketers should increase familiarity with heritage foods, particularly among potential domestic tourists, as familiarity may increase emotional values.